2010
DOI: 10.1111/j.1556-4029.2010.01520.x
|View full text |Cite
|
Sign up to set email alerts
|

The Recovery and Persistence of Salivary DNA on Human Skin

Abstract: Salivary DNA is encountered in many crimes, such as sexual assaults and murders. In this study, saliva from three male donors was deposited on the skin of three female recipients. The amount of male salivary DNA remaining on the female skin was measured over a 96-h period using the Quantifiler™ Y Human Male DNA Quantification Kit. In eight of the nine experiments, a full male DNA profile matching the donor was obtained even after 96 h. In addition, the study showed that the concentration of salivary DNA varied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…Kenna et al have reported that salivary DNA persists on the skin a minimum of 96 h (19). For example, it is possible to extract DNA from bite marks within this period, but amount of saliva deposited on the skin is usually very small in bite marks (19,20). In addition, the concentration of salivary DNA varied from donor to donor and from day to day (19).…”
Section: Sources Of Dnamentioning
confidence: 99%
See 3 more Smart Citations
“…Kenna et al have reported that salivary DNA persists on the skin a minimum of 96 h (19). For example, it is possible to extract DNA from bite marks within this period, but amount of saliva deposited on the skin is usually very small in bite marks (19,20). In addition, the concentration of salivary DNA varied from donor to donor and from day to day (19).…”
Section: Sources Of Dnamentioning
confidence: 99%
“…The gene that codes for an exacting protein contributes to only 2-5% of DNA, whereas the remaining 95% are non-coding DNA (25). Therefore we mark them as markers (19). However, some of these noncoding markers are linked with visible traits (3).…”
Section: Genotypingmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies conducted under controlled laboratory conditions have indicated that the DNA analysis of saliva placed on the skin of volunteers or cadavers may help in the identification of individuals (Sweet et al, 1997a;Anzai-Kanto et al, 2005;Kenna et al, 2011). However, the application of this approach to an actual criminal case has been reported only once before in forensic literature.…”
Section: Introductionmentioning
confidence: 99%